2006
DOI: 10.2118/103356-jpt
|View full text |Cite
|
Sign up to set email alerts
|

Tight Gas Sands

Abstract: Series articles are general, descriptive representations that summarize the state of the art in an area of technology by describing recent developments for readers who are not specialists in the topics discussed. Written by individuals recognized as experts in the area, these articles provide key references to more definitive work and present specific details only to illustrate the technology. Purpose: to inform the general readership of recent advances in various areas of petroleum engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
79
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(90 citation statements)
references
References 12 publications
(15 reference statements)
0
79
0
1
Order By: Relevance
“…Tight sandstone reservoirs show strong heterogeneities and have the geological characteristics of low porosity and low permeability [2,35], thus making it important to find a high-resolution time-frequency analysis method for the identification of hydrocarbon reservoirs. In this section, we attempt to apply the EWT-SET method to the field data, which is typical of tight sandstone reservoirs from the Zhongjiang gas field located in Western Sichuan, China.…”
Section: Hydrocarbon Detection Using Ewt-setmentioning
confidence: 99%
See 1 more Smart Citation
“…Tight sandstone reservoirs show strong heterogeneities and have the geological characteristics of low porosity and low permeability [2,35], thus making it important to find a high-resolution time-frequency analysis method for the identification of hydrocarbon reservoirs. In this section, we attempt to apply the EWT-SET method to the field data, which is typical of tight sandstone reservoirs from the Zhongjiang gas field located in Western Sichuan, China.…”
Section: Hydrocarbon Detection Using Ewt-setmentioning
confidence: 99%
“…However, global unconventional oil and gas resources are almost four times conventional oil and gas resources and the exploration of unconventional oil and gas is still stay in the developing stage [1]. Besides, unconventional reservoirs have complex geological structure and usually show poor petrophysical properties, such as strong heterogeneities, low porosity and permeability, which makes seismic signals more complex [2][3][4][5]. Therefore, it is necessary to find reliable methods, which can use seismic data directly for hydrocarbon detections in unconventional reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In 1970s, the U.S. government decided that the definition of TGR is one in which the expected value of permeability to gas flow would be less than 0.1 md [3]. Holditch [3] reported that the best definition of TGR is "a reservoir that cannot be produced at economic flow rates nor recover economic volumes of natural gas unless the well is stimulated by a large hydraulic fracture treatment or produced by use of a horizontal wellbore or multilateral wellbores".…”
Section: Introductionmentioning
confidence: 99%
“…Holditch [3] reported that the best definition of TGR is "a reservoir that cannot be produced at economic flow rates nor recover economic volumes of natural gas unless the well is stimulated by a large hydraulic fracture treatment or produced by use of a horizontal wellbore or multilateral wellbores". Some experts thought that the permeability should be between 0.1md and 0.0001md [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation